713Domestic violence and self-poisoning in Sri Lanka. (2nd September 2021) - Bandara, Piumee; Page, Andrew; Senarathna, Lalith; Kidger, Judi; Feder, Gene; Gunnell, David; Rajapakse, Thilini; Knipe, Duleeka
Abstract: Background: There is increasing evidence that domestic violence is an important risk factor for suicidal behaviour. The level of risk of domestic violence (DV) and its contribution to the overall burden of suicidal behaviour has not been quantified in South Asia, where 37% of suicide deaths globally occur. We examined the association between DV and self-poisoning in Sri Lanka through a large case-control study. Methods: Multivariable logistic regression models were conducted on 298 self-poisoning cases and 500 hospital controls to estimate the association between domestic violence and self-poisoning, and population attributable fractions (PAF) were estimated. Sensitivity analyses were conducted using 455 population-based controls. Results: DV exposure within the previous 12 months was strongly associated with self-poisoning for women (adjusted OR [AOR] 4·08, 95%CI 1·60-4·78) and men (AOR 2·52, 95%CI 1·51-4·21), compared to no abuse. Physical violence showed the highest risk among women, whereas among men, emotional abuse showed the highest risk (AOR 2·75, 95%CI 1·57-4·82). PAF% for exposure to at least one type of DV was 38% (95%CI 32-43) in women and 22% (95 CI 14-29) in men. Conclusions: DV was strongly associated with suicidal behaviour for men and women. Almost 40% of female self-poisoning cases and a fifth of male cases may be reduced if domestic violence is addressed. Key messages: The significant contribution of DV to the overall burden of self-poisoning suggests preventative and curative interventions to address domestic violence may yield significant gains in reducing suicidal behaviour in Sri Lanka, and other similar settings.